2016
DOI: 10.1007/s12039-016-1118-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular structure, spectroscopic investigations and computational study of a potential molecular switch of 2-([1,1’-biphenyl]-4-yl)-2-methyl-6-(4-nitrophenyl)-4-phenyl-1,3 diazabicyclo [3.1.0]hex-3-ene

Abstract: This work presents a combined experimental and theoretical study on a photochromic compound, 2-([1,1'-biphenyl]-4-yl)-2-methyl-6-(4-nitrophenyl)-4-phenyl-1,3 diazabicyclo [3.1.0]hex-3-ene, existing in closed form ('A') and open form ('B'). The spectroscopic properties of the title compound have been investigated by using IR, UV-Vis and 1 H NMR techniques. The molecular geometry and spectroscopic data of the title compound have been calculated by using the density functional method (B3LYP) invoking 6-311G(d,p) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The exciting discovery of optically controlled conduction and charge transport opens up the field of optoelectronic molecular switches. In the current study, the electrical current as the In the open form, the current approaches 60 μA at a voltage of 2 V. 63 Here, we have found that the T. canis parasite sequence turns on at = ℏ A 0.4 c er 0 0 and ω = 2 THz. In the on state, the current approaches 20 nA at V b = 20 V. We present a detection scheme for terahertz radiation on the DNA platform.…”
Section: ■ Discussionmentioning
confidence: 62%
“…The exciting discovery of optically controlled conduction and charge transport opens up the field of optoelectronic molecular switches. In the current study, the electrical current as the In the open form, the current approaches 60 μA at a voltage of 2 V. 63 Here, we have found that the T. canis parasite sequence turns on at = ℏ A 0.4 c er 0 0 and ω = 2 THz. In the on state, the current approaches 20 nA at V b = 20 V. We present a detection scheme for terahertz radiation on the DNA platform.…”
Section: ■ Discussionmentioning
confidence: 62%
“…Moreover, the symmetric CH 3 (νCH 3 ) and asymmetric CH 3 (ν as CH 3 ) stretching modes for the heterocyclic imidazole derivatives were calculated by DFT at 3031-3015 cm −1 and 2944 cm −1 and were recorded at 2895 and 2845 cm −1 in the IR spectrum, respectively. 38 In this work, we have observed the C-C stretching bands for the aromatic part of the title compound at 1647 and 1594 cm −1 and simulated them at 1576, 1572, and 1011 cm −1 by the B3LYP level, whereas this mode has been assigned as 1592, 1583, and 1009 cm −1 by the M06-2X level and 1610, 1601, and 1005 cm −1 by the HF method. Also, the C-C stretching modes contaminated with the in-plane C-H bending (IPB HCC) modes have been calculated at 1453, 1436, 1259, 1141, 1075, and 1015 cm −1 by the B3LYP level and recorded at 1461 cm −1 .…”
Section: Vibrational Analysismentioning
confidence: 94%
“…In the past, the aromatic C-C stretching modes for the imine oxime derivative were recorded at 1582 and 1579 cm −1 and simulated by the B3LYP/6-311++G(d, p) level at 1594 and 1577 cm −1 . 37 Also, Kanaani et al 38 recorded the aromatic C-H stretching signals for the phenyl rings of a heterocyclic imidazole compound in the range 3182-2929 cm −1 by FTIR spectroscopy and simulated them in the range 3048-3086 cm −1 by the B3LYP/6-311++G(d, p) level of the theory. Moreover, they 38 observed in-theplane (IPB) and out-of-the-plane (OPB) HCC bending modes in the range of 1334-1012 cm −1 and 926-560 cm −1 , respectively.…”
Section: Vibrational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the νC 14 H stretching band has occurred at 2829 cm −1 and has been assigned as a pure mode at 2823 cm −1 (96%). In the past, the ν as CH3 and νCH3 signals were recorded at 2895 and 2945 cm −1 and predicted by B3LYP in 3031–3015 cm −1 and 2944 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 56%